Effectiveness of the hypoxic exercise test to predict altitude illness and performance at moderate altitude in high-level swimmers - Pla, R.; Brocherie, F.; Le Garrec, S.; Richalet, J.-P. (Physiological Reports, 2020)
Purpose: The hypoxic exercise test is used to predict the susceptibility to severe High Altitude Illness (SHAI). In the present study, we aimed to use this test to predict the changes in performance and the physiological responses to moderate altitude in elite swimmers. Methods: Eighteen elite swimmers performed a hypoxic exercise test at sea level before a moderate 12-day altitude training camp (1,850 m) to determine if they were susceptible or not to SHAI. A maximal swimming performance test was conducted before (at sea level), during (at 1,850 m), and after (at sea level) the intervention. Arterial oxygen saturation (pulse oximetry), Lake Louise score, and quality of sleep questionnaire were collected every morning. The participants were classified in two groups, those who had a moderate to high risk of SHAI (SHAIscore = 3) and those who had a low risk of SHAI (SHAIscore < 3). Results: Seven swimmers presented a high risk of SHAI including three of them with a SHAIscore > 5. Pearson correlations indicated that SHAIscore was strongly correlated with the decrease in swimming performance at altitude (r = .60, p < .01). Arterial oxygen saturation during the hypoxic exercise test was the physiological variable that was best related to performance decrease at altitude (r = .54, p < .05). No differences were observed for Lake Louise score and quality of sleep between swimmers who suffered from SHAI or not (p > .1). Conclusion: In a population of elite swimmers, the combination of clinical and physiological variables (SHAIscore, oxygen desaturation) estimated the performance decrease at moderate altitude. The hypoxic exercise test could allow coaches and scientists to better determine the individual response of their athletes and manage the altitude acclimatization.